Dendritic spine loss caused by AlCl3 is associated with inhibition of the Rac 1/cofilin signaling pathway. (December 2018) - Yang, Xu; Cao, Zheng; Zhang, Jian; Shao, Bing; Song, Miao; Han, Yanfei; Li, Yanfei
Abstract: Aluminum (Al) has neurotoxicity that can result in cognitive dysfunction. Hippocampal dendritic spine loss is a pathological characteristic of cognitive dysfunction. Our previous study reported that Al exposure caused dendritic spine loss in the hippocampus, but the underlying mechanism remains unclear. In this study, rats were orally administered 50, 150 or 450 mg/kg of AlCl3 for 90 days. The dendritic spine density of the CA1 and DG regions was detected by Golgi-Cox staining. The F-actin/G-actin ratio, the expression of drebrin A and the components of the Rac 1/cofilin pathway were measured in the hippocampus. The results obtained showed that AlCl3 caused dendritic spine loss and decreased the F-actin/G-actin ratio. In addition, it was found that AlCl3 downregulated the expression of Rac 1, p-PAK, p-LIMK, p-cofilin and drebrin A and upregulated cofilin expression. Altogether, these results demonstrated that Al inactivated the Rac 1/cofilin pathway by inhibiting the phosphorylation of cofilin and the polymerization of F-actin, resulting in dendritic spine loss in the hippocampus. Graphical abstract: Image 1 Highlights: AlCl3 exposure caused dendritic spine loss in CA1 and DG regions of hippocampus. AlCl3 decreased the F-actin/G-actin ratio in hippocampus. AlCl3 inhibits the Rac 1/cofilin pathway component expression. Abstract : AlCl3 triggered the hippocampal dendritic spine loss via inhibiting the Rac 1/cofilin signaling pathway.